EFFICIENCY OF EU FINANCIAL SUPPORT POLICY FOR DEVELOPMENT OF RURAL ENTREPRENEURSHIP IN POLAND - Wasilewski, Adam (Economics of Agriculture, 2015)
The main research objective was to assess the effciency and effectiveness, in some theoretical approaches considered as a type of effciency, of EU fnancial support affecting the entrepreneurship development in rural areas of Poland. Descriptive and comparative analysis of basic statistics and Gini coeffcient as well as the econometric model of absolute beta convergence were applied as e research methods. The analysis utilised the data from Central Statistical Offce, Local Data Bank, for 2004-2013 for 1,529 rural counties. General conclusion of the paper is that EU fnancial support had a positive and statistically signifcant impact on local absolute beta convergence. Moreover, the analyses confrmed that the higher level of support from the EU budget accelerates an increase in the number of private enterprises, micro-enterprises and the number of the employees. It also slows down the processes of growth in the number of the unemployed. However this is the shorttime effect.